An analysis of teacher questions and corresponding pupil responses in selected elementary science classes - Angeles, Amparo O. (1972)
An analysis of teacher questions and corresponding pupil responses in selected elementary science classes was made in this study. Five public elementary schools were selected to compose the school sample. Thirty class recitations were recorded and analyzed. Of the eleven categories of pupil responses identified in the lesson transcripts, the most frequently observed pupil response behavior is the Designating type of pupil response, followed by the Describing-Attributive. Question patterns observed may be investigated further to ascertain their capability to elicit particular response category.
Mimeographed.
Thesis (M.A.T. Elementary Science)--University of the Philippines, Quezon City.
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Zamboanga del Norte